Centers of Hadith Learning and Literature in the Islamic World - Ujang Sahid; Engkos Kosasih; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Centers of Hadith learning and literature in the Islamic world play a crucial role in disseminating, preserving and developing understanding of hadith, which is an important source in Islam. This article highlights the definition and important role of these centers in the sustainability of Islamic intellectual heritage. Hadith learning centers are academic institutions and libraries that specialize in the study, research, and teaching of hadith, Establishing a strong basis for comprehending the principles of the religion In the Islamic world, Al-Azhar University is recognized as one of the main centers for hadith studies and literature., Madrasah al-Nizamiyah in Baghdad, and Dar al-Hadith al-Ashrafiyah in Yemen. They are not only centers of academic activity, but also guardians of Islamic intellectual heritage.The main contribution of these centers lies in the development of hadith research methodologies, such as hadith criticism and historical approaches. The author uses an interdisciplinary approach that combines traditional methods with contemporary approaches to increase understanding of hadith.Thus, centers of hadith learning and literature in the Islamic world not only facilitate study and research, but also Contribute significantly to the preservation and enhancement of Islamic intellectual traditions through the use of relevant research methods.